2018
DOI: 10.31768/2312-8852.2018.40(3):190-193
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Morphine Treatment on Bladder Cancer Cell Proliferation and Apoptosis: In Vitro Studies

Abstract: Aim: The aim of this study was to determine the effect of morphine on bladder cancer cell proliferation and apoptosis in vitro. Materials and Methods: MTT assay was used to measure percentage growth of RT-112 human bladder cancer cells after 72 hours of morphine/morphine + naloxone treatment. Expression of µ-opioid receptors was assessed by Western blot and finally, apoptotic assay with CellEvent Caspase-3/7 Green Detection Reagent was carried out using confocal microscopy. Results: The MTT assays showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Our observations are in line with previous investigations indicating that antagonists of MOR-1 reduce tumorigenesis, metastatic behaviors, and EMT in the presence or absence of the agonists of the receptor (Bimonte et al, 2018;Lennon et al, 2014;Mathew et al, 2011). Naloxone (a MOR-1 antagonist) inhibited the antiapoptotic effects of morphine in RT-112 bladder cancer cells (Harper et al, 2018). Mathew et al (2011) have shown that MNTX at 10 and 100 nM significantly inhibited invasion in Lewis lung carcinoma cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations are in line with previous investigations indicating that antagonists of MOR-1 reduce tumorigenesis, metastatic behaviors, and EMT in the presence or absence of the agonists of the receptor (Bimonte et al, 2018;Lennon et al, 2014;Mathew et al, 2011). Naloxone (a MOR-1 antagonist) inhibited the antiapoptotic effects of morphine in RT-112 bladder cancer cells (Harper et al, 2018). Mathew et al (2011) have shown that MNTX at 10 and 100 nM significantly inhibited invasion in Lewis lung carcinoma cells.…”
Section: Discussionsupporting
confidence: 92%
“…Harper et al considered the effects of morphine on the proliferation of the RT112 human UCC cell line. 43 A dose responsive proliferative effect was observed with exposure to morphine (7% increase at a 62.5 mm dose vs control, p[0.0079), which was attenuated by pretreatment of the cells with naloxone. Dot blot and Western blots were inconclusive for baseline MOP expression.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 98%
“…The information obtained about lidocaine could direct researchers to screen more local anesthetics for their cancer-inhibiting capabilities. Indeed, many local anesthetics have been confirmed to possess anticancer efficacies, such as morphine ( Kim et al, 2016 ; Chen et al, 2017 ; Nishiwada et al, 2019 ), although it demonstrates contrasting results in cancer treatment ( Harper et al, 2018 ; Tuerxun and Cui, 2019 ); procaine ( Ma et al, 2016 ; Li C. et al, 2018 ; Li Y.C. et al, 2018 ); ropivacaine ( Piegeler et al, 2015 ; Gong et al, 2018 ; Wang et al, 2019 ; Yang J. et al, 2019 ); bupivacaine ( Xuan et al, 2016 ; Dan et al, 2018 ); and levobupivacaine ( Jose et al, 2018 ; Li et al, 2019 ); as well as propofol ( Xu et al, 2018 ; Kang et al, 2019 ; Zheng et al, 2019 ), etc.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%